(3GdYOIs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3eMeO Hf Ydj Hf jMji GdefUhQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3EedGA eNJUQ aj CUhd Gdabg JMjW HLejY CHhGHg Ydi SHjd GdEjLGR hGdGNJUGQ(B... (3aUd aj eGgjI CUhd Gdabg(B...s
(3BNQgG (B:s
(3hCeG GdeHGMK abO HjfG Cf WQjb GdYde HgG cdgG GdTQY Ydi eG eVi Gdbhd ajgG(B... (3hdh TQYfG aj TQM Pdc dWGd GdcJGH hajeG dNUfGg caGjI(B...s
(3ebGHdI heUMMIs
(3JHUQI GdYfhGf (B:s
(3GdYOI aj CUhd Gdabgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3GdCYdGe(B: (3L(B6(3, U(B84s
Keywords: (3CUhd Gdabgs